Socio-ecological factors shape the opportunity for polygyny in a migratory songbird. (13th February 2020) - Canal, David; Schlicht, Lotte; Manzano, Javier; Camacho, Carlos; Potti, Jaime
Abstract: Why females pair with already mated males and the mechanisms behind variation in such polygynous events within and across populations and years remain open questions. Here, we used a 19-year data set from a pied flycatcher ( Ficedula hypoleuca ) population to investigate, through local networks of breeding pairs, the socio-ecological factors related to the probability of being involved in a polygynous event in both sexes. Then, we examined how the breeding contexts experienced by individuals shaped the spatial and temporal separation between broods of polygamous males. The probability of polygyny decreased with the distance between nests. Indeed, secondary females were often close neighbors of primary females, although the distance between both nests increased slightly with increasing synchrony between them. The probability of polygyny was also related to the breeding time of individuals because early breeding males were more likely to become polygynous with late-breeding females. Throughout the season, there was substantial variation in the temporal separation between primary and secondary broods, and this separation was, in turn, related to the breeding asynchrony of the polygamous males (in the primary nest) relative to the neighbors. Polygynous males that bred late relative to their neighbors had a short time window to attract a second female and, thus, the breeding interval between their primary and secondary broods was reduced. Overall, the spatial proximity between polygynous males' broods and, if the opportunity existed, their temporal staggering are compatible with a male strategy to maximize paternity and reduce the costs of caring for two broods, though the effect of female's interest, either primary or secondary, cannot be fully ruled out. We highlight that a comprehensive assessment of the breeding contexts faced by individuals is essential to understand mating decisions and reconcile the discrepancies raised by previous work on social polygyny. Lay Summary: Local social-ecological contexts determine mating decisions in a songbird. Using a novel approach that allows consideration of the local breeding contexts faced by each individual in the population, we show that breeding time in relation to the neighbors is key to become both polygynous (males) and secondary (females). Further, the spatial and temporal separations between polygynous males' broods, which vary substantially throughout the season, arise mainly from the males' own interests to maximize paternity.